2018
DOI: 10.1007/s10068-018-0352-y
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity and contents of leaf extracts obtained from Dendropanax morbifera LEV are dependent on the collecting season and extraction conditions

Abstract: This study compared the antioxidant activity of extracts from Dendropanax morbifera (D. morbifera) Levillis leaves. The concentrations of flavonoids and polyphenols were measured in extracts of D. morbifera leaves. The antioxidant activities were examined by ABTS and DPPH radical scavenging activity and ferric reducing antioxidant power (FRAP). Total flavonoid and polyphenol contents, and FRAP were highest in the 30% ethanol extract collected in May. The ABTS and DPPH radical scavenging activities were the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 35 publications
4
32
1
Order By: Relevance
“…In the present study, the highest ABTS activity was recorded when DPS was extracted using 60% ethanol concentration. Similar trend was also obtained by [55], where 60% of ethanol concentration yielded the highest ABTS radical scavenging activity of Dendropanax morbifera (D. morbifera) Levillis leaves. Figure 2f shows the relationship between temperature and ethanol concentration on ABTS activity at a constant extraction time of 60 min.…”
Section: Optimum Extraction Condition Based On Abts Activitysupporting
confidence: 82%
“…In the present study, the highest ABTS activity was recorded when DPS was extracted using 60% ethanol concentration. Similar trend was also obtained by [55], where 60% of ethanol concentration yielded the highest ABTS radical scavenging activity of Dendropanax morbifera (D. morbifera) Levillis leaves. Figure 2f shows the relationship between temperature and ethanol concentration on ABTS activity at a constant extraction time of 60 min.…”
Section: Optimum Extraction Condition Based On Abts Activitysupporting
confidence: 82%
“…In general, phenolic compounds prevent free radicals from acting in the body and, since they protect molecules, such as DNA, they may interrupt some carcinogenic processes. According to Youn et al (2019), methodologies which use scavenging of radicals DPPH, ABTS and FRAP measure the activity of compounds of hydrophilic nature, i. e., compounds with high polarity. Therefore, antioxidant activities observed by this study may be directly connected with flavonoids in extracts under investigation.…”
Section: Antioxidant and Anti-listeria Monocytogenes Activitiesmentioning
confidence: 99%
“…Thaipong et al [38], studying the comparison among ABTS, DPPH, FRAP, and ORAC assays for estimating the antioxidant activity of guava fruit extracts, also demonstrated that FRAP test showed high correlation with total phenolic content. Youn et al [39] also investigated the relationship between antioxidant activity and polyphenol or flavonoid contents in leaf extracts obtained from Dendropanax morbifera LEV. and showed that FRAP value was strongly correlated with polyphenols.…”
Section: Resultsmentioning
confidence: 99%